Gaya Kepemimpinan Transformasional dan Keberlanjutan Sistem Akuntansi Digital: Perspektif Kemudahan dan Kemanfaatan Pengguna - Sukmawati, Aegisia; Maisyarah, Nyimas Dian; Murnidayanti, Scheilla Aprilia; Dahlia, Dahlia (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to investigate the influence of transformational leadership style on the intention to continue using digital accounting systems, particularly analyse perceived ease of use and perceived of usefulness as mediating factors. Research data were utilized purposive sampling technique and collected through online survey for digital accounting systems users in private and public sectors in Indonesia. The final dataset consisted of 55 respondents. The data collected is analysed using SEM-PLS with Smart-PLS 4 software. The results confirm that transformational leadership style did not directly influence to continuance intention to use digital accounting system. However, it influences continuance intention to use digital accounting systems through intervention perceived of usefulness as full mediator. In contrast, variable perceived ease of use did not show as a mediator. This finding is attributed to the characteristic respondents of this study that have high proficiency. These research findings contribute to the strategic function of leaders to shape employee perceptions regarding digital accounting systems. Furthermore, the study suggests that organizations should not solely focus on technical operational skills training. It should go beyond to change employee mindsets, ensuring employees’ recognition and derive actual value from the digital accounting systems utilized.